Pediatric Mechanical Circulatory Support: Pathophysiology of Pediatric Hemostasis and Available Options - Giorni, Chiara; Rizza, Alessandra; Favia, Isabella; Amodeo, Antonio; Chiusolo, Fabrizio; Picardo, Sergio G.; Luciani, Matteo; Di Felice, Giovina; Di Chiara, Luca (Frontiers in Cardiovascular Medicine, 2021)
Pediatric mechanical circulatory support (MCS) is considered a strategy for heart failure management as a bridge to recovery, transplantation or as a destination therapy. The final outcome is significantly impacted by the number of complications that may occur during MCS. Children on Ventricular Assist Devices (VADs) and Extracorporeal Membrane Oxygenation (ECMO) are at high risk for bleeding and thrombotic complications that are managed through anticoagulation. The first detailed guideline in pediatric VADs (Edmonton Anticoagulation and Platelet Inhibition Protocol) was based on conventional antithrombotic drugs, as unfractionated heparin (UFH) and warfarin. UFH is the first line anticoagulant in pediatric MCS, although its profile is not considered optimal in pediatric setting. The broad variation in heparin doses among children is associated to frequent occurrence of cerebrovascular accidents, bleeding and thrombocytopenia. Direct thrombin inhibitors (DTIs) have been utilized as alternative strategies to heparin. Since 2018 bivalirudin has become the chosen anticoagulant in the long-term therapy of patients undergoing MCS implantation, according to the most recently protocols shared in North America. This article provides a review of the non-traditional anticoagulation strategies utilized in pediatric MCS, focusing on pharmacodynamics, indications, doses and monitoring aspects of bivalirudin. Moreover, it exposes the efforts and the collaborations among different specialized centers, which are committed to an ongoing learning in order to minimize major complications in this special pediatric population. Further prospective trials regarding to DTIs in pediatric MCS setting are necessary and in specific well-designed randomized control trials between UFH and bivalirudin. To conclude, based on the reported literature, the clinical use of the bivalirudin in pediatric MCS seems to be a value added in controlling and maybe reducing thromboembolic complications. Further research is necessary to confirm all the results provided by this literature review.